1996
DOI: 10.1159/000139380
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interactions and Interindividual Variability of Ciclosporin Metabolism in the Small Intestine

Abstract: The undecapeptide ciclosporin is used as immunosuppressant after organ transplantation and for therapy of immune diseases. Low and variable bioavailability of ciclosporin has been attributed to its metabolism in the small intestine. The aim of the present study was to investigate drug interactions and interindividual variability of ciclosporin metabolism in the small intestine. Ciclosporin metabolism was studied in vitro using microsomes isolated from the small intestine of humans and pigs. The metabolites gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 17 publications
3
35
2
Order By: Relevance
“…No clear relationship between sex and CL/F had been previously established for ciclosporin. A sex-dependent racial difference in the disposition of ciclosporin was reported in a small number of healthy patients [35] and in vitro studies have suggested that women clear CYP3A4 substrates more rapidly than men do, which may result in a higher apparent volume of distribution and CL/F [36] , in apparent contradiction with the present results. The influence of this covariate needs to be confirmed as the observed effect could be due to confounding factors.…”
Section: Discussioncontrasting
confidence: 99%
“…No clear relationship between sex and CL/F had been previously established for ciclosporin. A sex-dependent racial difference in the disposition of ciclosporin was reported in a small number of healthy patients [35] and in vitro studies have suggested that women clear CYP3A4 substrates more rapidly than men do, which may result in a higher apparent volume of distribution and CL/F [36] , in apparent contradiction with the present results. The influence of this covariate needs to be confirmed as the observed effect could be due to confounding factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Although the blood drug concentrations are well below the associated K m for CYP3A4 (4 -7 M for cyclosporine, tacrolimus, and sirolimus) (Lampen et al, 1995(Lampen et al, , 1996(Lampen et al, , 1998 and P-gp (8 M for cyclosporine) (Saeki et al, 1993), the intracellular concentrations in enterocytes and hepatocytes may be higher, resulting in a transition to nonlinear kinetics for cyclosporine.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the metabolism of cyclosporine and tacrolimus decrease when they are co-administered with drugs that act as substrates and/ or inhibitors for CYP3A4. 8,9) In addition, cyclosporine enhances the plasma concentrations of several drugs such as atorvastatin and repaglinide, which are metabolized by CYP3A4, whereas tacrolimus has no eŠect on atorvastatin pharmacokinetics ( Table 1). [10][11][12][13][14][15][16] However, there are few in vitro studies comparing the eŠects of the immunosuppressants on human hepatic CYP-mediated drug-metabolizing activity under the same experimental conditions.…”
Section: Introductionmentioning
confidence: 99%